Politisasi Kepala Desa (Studi Analisis Wacana Penundaan Pemilu) - Djoni Gunanto; Muhammad Sahrul (Jurnal Inovasi dan Kreativitas (JIKa), 2023)
Problem: The Village Head is the head of the village government organization who has a strategic position and has broad responsibilities. Apdesi's presence in public coincided with the discourse on extending the President's term of office which resurfaced after several political parties in the Government's coalition, namely Golkar, PKB, and PAN conveyed to the public about extending the President's term of office. The postponement of the election was then rolled back with the support of village heads throughout Indonesia. This was conveyed by the Chairperson of Apdesi Surtawijaya who said the declaration would be made per region from Sabang to Merauke. He said the movement would start with the installation of a banner supporting Jokowi for 3 periods. Purpose : To analyze the politicization of village heads in the discourse on postponing elections Methodology: using filter review by understanding and analyzing academic texts, journals and the results of scientific seminars. Findings : The village head in the world of politics causes a lot of debate. The demand for the Village Head to be neutral in political parties began to resonate. The first declaration violated the Village Law. Second, violating political ethics for stealing the start of the campaign. what was done by the village head in the APDESI Silatnas became part of a political campaign or activity, not as an aspiration with the result of a conclusion Politicization of the village head's bureaucracy in the form of Jokowi's declaration of 3 periods in the election which was wrapped in the postponement of the election for various justification reasons has its own meaning for the community because it exists to perpetuate power Paper Type: Literature Review